Teaching Counseling Skills in Audiology Graduate Programs: Clinical Supervisors’ Perceptions and Practices - Muñoz, Karen; Landon, Trent; Corbin-Lewis, Kim (Journal of the American Academy of Audiology, 2018)
Counseling is a critical component within audiological service delivery. Partnering with patients to support them in learning to effectively cope with their hearing challenges is a key component in achieving desired outcomes. Even though there is agreement on the foundational role counseling plays in audiology service delivery, counseling instruction varies among audiology training programs.The purpose of this study was to investigate the perspectives and practices of supervisors in audiology graduate training programs related to mentoring students in the acquisition of counseling skills.A cross-sectional design was used; participants completed a self-report survey.The survey was sent to 323 clinical supervisors in AuD graduate programs in the United States.Completed surveys were received from 205 supervisors. Responses were analyzed using descriptive statistics to identify practice trends.Participants reported their perceptions about importance of teaching counseling skills to audiology students, their confidence in teaching skills, their self-efficacy for supporting student learning, how they provide feedback to students, and challenges they encounter. Most participants reported their program requires a counseling course (88%; n = 176). Most of the participants reported confidence in teaching counseling skills; however, fewer reported being very or extremely confident in teaching students how to talk with clients about their emotions (53%; n = 109) and explaining the rationale behind specific counseling strategies (47%; n = 97). Participants with more years of supervisory experience had statistically significantly higher self-ratings for teaching confidence and self-efficacy for supporting student learning in counseling than those with fewer years of experience.Audiology supervisors in AuD programs believe counseling is important to teach to students; however, they report variability in use of methods for providing feedback, evaluating student performance, and in their self-efficacy for supporting student learning. Future audiologists would benefit from a more systematic approach within graduate training for teaching counseling skills.
Keywords: audiology; counseling; supervision